1994
DOI: 10.1523/jneurosci.14-03-01153.1994
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor increases nicotinic ACh receptor gene expression and current density in wild-type and protein kinase A-deficient PC12 cells

Abstract: We thank D. Phillips for technical assistance, J. Wagner for the 123.7 cells, J. Boulter for providing nAChR cDNA clones, S. Froehner for use of his peristaltic pump, J. Dunlap for use of his densitometry equipment, and J. Margiotta and J. Wagner for comments on the manuscript, and P.D.G. thanks B.P. for inspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 78 publications
8
65
0
Order By: Relevance
“…NGF-driven differentiation of PC12 cells has been extensively used as a model system to study the physiological, biochemical, and molecular mechanisms of neurotrophin signaling. In regard to neuronal nAChR, it has been demonstrated that in PC12 cells, NGF increases ACh-induced channel activity and ACh-induced macroscopic current density (4,21,48), phenomena that are thought to be a consequence of an increase in the number of functional nAChR (21). This hypothesis is consistent with observed increases in the binding of [ 3 H]nicotine (49) and of anti-nAChR antibodies (50) that occur in PC12 cells in response to NGF.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…NGF-driven differentiation of PC12 cells has been extensively used as a model system to study the physiological, biochemical, and molecular mechanisms of neurotrophin signaling. In regard to neuronal nAChR, it has been demonstrated that in PC12 cells, NGF increases ACh-induced channel activity and ACh-induced macroscopic current density (4,21,48), phenomena that are thought to be a consequence of an increase in the number of functional nAChR (21). This hypothesis is consistent with observed increases in the binding of [ 3 H]nicotine (49) and of anti-nAChR antibodies (50) that occur in PC12 cells in response to NGF.…”
Section: Discussionsupporting
confidence: 60%
“…Among the neuronal genes whose expression is up-regulated in response to NGF in PC12 cells are the genes encoding several subunits (␣3, ␣5, ␣7, ␤2, and ␤4) of neuronal nicotinic acetylcholine receptors (nAChRs) (21)(22)(23). nAChRs are pentameric ligand-gated ion channels important for synaptic transmission in the nervous system (24).…”
Section: Nerve Growth Factor (Ngf)mentioning
confidence: 99%
See 1 more Smart Citation
“…S4). In these experiments, we used neuronally differentiated PC12 cells that predominantly express a3b4 nAChR subtype (Avila et al, 2003;Henderson et al, 1994) and gave larger and more reproducible amperometric responses to ACh as found by us and other investigators (Nery et al, 2010) compared with un-differentiated PC12 cells.…”
Section: Effect Of Human Cst Variants On Blockade Of Acetylcholine-evmentioning
confidence: 89%
“…It is important to determine if this effect extends to nAChR protein expression given the functional implications of such regulation. To address this critical issue, we used the rat pheochromocytoma cell line, PC12, which expresses relatively high levels of nAChR subunits following nerve growth factor treatment (Henderson et al 1994). PC12 cells were transfected with either miR-542-3p mimic or inhibitor followed by 3 d of nerve growth factor treatment and subsequent immunoblotting.…”
Section: Mirna Regulation Of Endogenous Nachr Expressionmentioning
confidence: 99%